The role of marketing communications in developing the performance of tourism companies An analytical study of a sample of employees in tourism companies in Erbil city / Kurdistan Region - Walaa Judith Jaff; Zain Nuri Ismail (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This study aims at identifying the role of marketing communication in developing the performance of tourism companies in Erbil/ Kurdistan region of Iraq. To come to that end, the researcher adopted the analytical descriptive approach (to fit the nature of the study) by analysing the effect of the independent variable which stand for information technology with all its aspects (decision making, service activities, financial and administrative issues, and information technology) and the effect of the second independent variable which stands for commercial communication with all its aspects (activating sales, advertisements, publication, commercials, public relationship) on the dependent variable which is the performance of tourism companies with all its aspects (the increase in the number of tourists, the increase in revenues, developing the efficiency of the services, the efficiency of the performance of the employees in the human resource management, and organization). A questionnaire was developed to collect the data of the study, and it was given to judges and specialists and the recommended modifications were carried out. The questionnaire was then distributed on a random sample of travel and tourism offices in Erbil where 217 questionnaires were distributed, and the valid ones were 200. The data was analysed by means of SPSS version 24. The following results were attained. Tourist offices vary in terms of its performance in relation to variations with regard to how much it makes use of marketing communication. Marketing communication has a positive and significant effect in the performance of tourism companies.